OFC/NFOEC 2008 - 2008 Conference on Optical Fiber Communication/National Fiber Optic Engineers Conference 2008
DOI: 10.1109/ofc.2008.4528116
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Fault-Tolerant All-Optical Multicast Networks via Network Coding

Abstract: Network coding, an emerging field of research, provides a means to create efficient alloptical multicast networks that feature hitless reconfiguration. Here a photonic bitwise exclusive-OR hardware element supplies the key enabling functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…This can be accomplished by converting the optical signal to an electronic symbol, performing the operations using normal electronic computations, and then converting the result back into an optical signal for retransmission. This constant optical-electical-optical conversion and stopping/buffering of the flow is undesirable, and so the use of all-optical XOR gates for coding operations has been explored [5], [6], [7]. Using only XOR gates, however, limits coding operations to simple addition whereas most networking coding applications also require at least some scalar multiplication in the computing of a linear combination.…”
Section: B Static Network Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be accomplished by converting the optical signal to an electronic symbol, performing the operations using normal electronic computations, and then converting the result back into an optical signal for retransmission. This constant optical-electical-optical conversion and stopping/buffering of the flow is undesirable, and so the use of all-optical XOR gates for coding operations has been explored [5], [6], [7]. Using only XOR gates, however, limits coding operations to simple addition whereas most networking coding applications also require at least some scalar multiplication in the computing of a linear combination.…”
Section: B Static Network Codingmentioning
confidence: 99%
“…Kamal et al proposed network-coding schemes for survivable optical networks [2], [3], [4] in which electronic network coding operations supported the optical protection schemes. Menendez and Gannet [5] proposed performing the coding operations for survivability at the optical layer using alloptical XOR logic gates, and Hisano et al [6] and An et al [7] recently demonstrated network coding functionality using all-optical XOR logic gates. We investigated optical switch and optical network coder architectures which would provide unrestricted digital network coding capabilities at the optical layer [8], and Liu et al applied an asynchronous network coding strategy at the optical layer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Menendez and Gannet [7] proposed to use photonic XOR devices for network coding and show its operation with cross-session coding of two multicast sessions with a shared link. Liu et.al.…”
Section: Related Work and Our Contributionmentioning
confidence: 99%
“…The results confirm that the proposed MSMR scheme can obtain the obvious diversity gain with considering the effects of scintillation, thermal noise, background noise, and multiuser interference, and the rapid convergence property has been demonstrated by Extrinsic Information Transfer (EXIT) chart. Compared with the MSMR scheme requiring multiple relay nodes [18], in this paper, one single relay node is sufficient for serving the multisource, saving the equipment cost.Currently, a new form of cooperative relay method, known as network coding, has attracted tremendous interest [12][13][14][15]. It can increase the system throughput and transmission robustness.Menendez and Gannet [12] proposed a photonic XOR network coding technique for efficient and fault-tolerant all-optical networks.…”
mentioning
confidence: 99%